2021
DOI: 10.1038/s41598-021-87399-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid neural network based on novel audio feature for vehicle type identification

Abstract: Due to the audio information of different types of vehicle models are distinct, the vehicle information can be identified by the audio signal of vehicle accurately. In real life, in order to determine the type of vehicle, we do not need to obtain the visual information of vehicles and just need to obtain the audio information. In this paper, we extract and stitching different features from different aspects: Mel frequency cepstrum coefficients in perceptual characteristics, pitch class profile in psychoacousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Researchers [77] classify accelerating vehicles using audio and apply random noise and pitch shift to expand their dataset. Other work [14] focuses on vehicle type identification using MFCCs and other audio features, these authors apply city noise to augment captured signals. There have been additional applications of augmentation to acoustic vehicle DL related tasks [7,13,53].…”
Section: Audio Data Augmentationmentioning
confidence: 99%
“…Researchers [77] classify accelerating vehicles using audio and apply random noise and pitch shift to expand their dataset. Other work [14] focuses on vehicle type identification using MFCCs and other audio features, these authors apply city noise to augment captured signals. There have been additional applications of augmentation to acoustic vehicle DL related tasks [7,13,53].…”
Section: Audio Data Augmentationmentioning
confidence: 99%
“…Piczak 4 first proposed the use of 2-D CNN to learn Log-Mel spectrogram features, which has significantly improved ESC performance compared with traditional machine learning algorithms such as KNN and SVM. Chen et al 5 accurately identified the audio signal of the vehicle by fusing the LSTM unit into the convolutional neural network. Boddapati et al 6 uses AlexNet 7 and GoogLeNet 8 to classify the environmental sound features extracted from the spectrum.…”
Section: Related Workmentioning
confidence: 99%
“…Mel-frequency cepstral coefficients (MFCCs) are used in conjunction with ML or deep learning (DL) as features in a number of existing AVDI systems: in [8] they are used with a modified MLP, in [5] they are extracted from a specific high energy audio region and used with an ANN and knearest neighbors (KNN) classifier, and in [9] they are used in a feature set containing the pitch class profile (PCP) and short-term energy (STE) of vehicle audio signals in a hybrid convolutional neural network (CNN) containing a long shortterm memory (LSTM) layer.…”
Section: Related Workmentioning
confidence: 99%
“…[5] MFCC KNN /ANN [6] DFT SVM [7] STFT SVM [8] MFCC MLP [9] MFCC CNN /PCP/STE /LSTM [10] Mod-PCEN SNN [11] GCC RANSAC [12] GCC RANSAC [13] DWT LR architecture in which information acquired at sub-Nyquist rates from different frequency bands is used in a range of applications without prior signal reconstruction.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation